2002
DOI: 10.1016/s0736-0266(01)00080-8
|View full text |Cite
|
Sign up to set email alerts
|

In situ cell nucleus deformation in tendons under tensile load; a morphological analysis using confocal laser microscopy

Abstract: Cell and cell nucleus deformations have been implicated in the mechanotransduction of mechanical loads acting on tissues. While in situ cell nucleus deformation in response to increasing tissue strains has been examined in articular cartilage this phenomenon has not been investigated in tendons. To examine in situ cell nuclei deformation in tendons undergoing tensile strain rat tail tendons were harvested from adult Sprague-Dawley rats and stained with acridine orange to highlight the cell nuclei. The tendons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
112
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 47 publications
(22 reference statements)
13
112
2
1
Order By: Relevance
“…9,18,21,31,32 Tensile loading of rat tail tendons has been shown to result in fluid flow, 25,26 and cellular deformations. 24 Both of these mechanisms have previously been associated with a decrease in cilia length. Fluid flow has been shown to decrease cilia lengths in renal cells 18,21,31,32 and loss of primary cilia from the endothelial surface of human umbilical cord cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,18,21,31,32 Tensile loading of rat tail tendons has been shown to result in fluid flow, 25,26 and cellular deformations. 24 Both of these mechanisms have previously been associated with a decrease in cilia length. Fluid flow has been shown to decrease cilia lengths in renal cells 18,21,31,32 and loss of primary cilia from the endothelial surface of human umbilical cord cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 While the precise mechanism(s) which trigger these changes in cilia length are unknown, it has been suggested that fluid flow and cell deformation are associated with decreases in cilia length, 9,[19][20][21] while increases in cilia length have been associated with cytoskeletal disruption. 22 Studies from our lab have shown that stress-deprivation (SD) of tendon cells has been associated with a disruption of cytoskeletal organization, 23 while tensile loading of tendons has been associated with cell deformation 24 and extracellular fluid flow. 25,26 Therefore, the purpose of the current study was to examine the effect of loading conditions on the length of primary cilia of rat tail tendon cells in situ.…”
mentioning
confidence: 99%
“…We also hypothesized this change in mechanoresponsiveness was due to an alteration in the mechanostat set point of the cells and was not a result of any substantial change in the material properties of these stress-deprived tendons. The stress-deprived in vitro system used in the current study is intended to model the destructive mechanism(s) that are thought to precede the overt pathological development of tendinopathy, namely, the catabolic response of tendon cells to the local loss of homeostatic strain as a result of isolated, microscopic collagen fiber damage [4,28]. While the concept that understimulation, rather than overstimulation, of tendon cells may be at the heart of the etiopathogenesis of tendinopathy is a new concept [5], we believe our previous investigations [3,4,33,34,36] have validated this model as a useful tool to investigate the potential role of mechanobiology in the etiopathogenesis of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The stress-deprived in vitro system used in the current study is intended to model the destructive mechanism(s) that are thought to precede the overt pathological development of tendinopathy, namely, the catabolic response of tendon cells to the local loss of homeostatic strain as a result of isolated, microscopic collagen fiber damage [4,28]. While the concept that understimulation, rather than overstimulation, of tendon cells may be at the heart of the etiopathogenesis of tendinopathy is a new concept [5], we believe our previous investigations [3,4,33,34,36] have validated this model as a useful tool to investigate the potential role of mechanobiology in the etiopathogenesis of tendinopathy. The increase in MMP-13 mRNA expression and protein synthesis seen in this model [2,5,[33][34][35][36], as well as the histological features of cell shape change [21] and apoptosis [2,12], which accompany loss of homeostatic strain, are very similar to those changes reported in clinical cases of tendinopathy [1, 2, 5, 19, 24, 26, 28, 30, 31, 38-40, 45, 50, 54, 60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…The responsiveness of connective tissue cells such as osteoblasts, chondrocytes and fibroblasts to mechanical strain has been confirmed by several in vitro investigations and the effect of cyclic strain on tendon cells has been associated with a diverse array of biological responses [ 1- 3,6,5,12,19,24,30,38,46,47,49,53,54]. These cellular features are necessary to restore the normal mechanical properties of the tissue after injury or during a remodeling process (e.g.…”
Section: Discussionmentioning
confidence: 99%